Modulación de la respuesta inmune en juveniles de tilapia roja (Oreochromis mossambicus x O. niloticus) con inclusión de β-glucano en dieta - Andrade Aldean, Brandon Gustavo (2021)
β-glucans are the most widely used immunostimulants in fish, which are generally based on structures of microorganisms that stimulate the innate immune system, helping the health of the animals and increasing the resistance of pathogens, survival and preparing the fish for critical situations. In this research, the immune response was evaluated in juvenile red tilapia (Oreochromis mossambicus x O. niloticus) with inclusion of β-glucan in the diet, the research was carried out in El Vergel in the Canton of Valencia. The variables to evaluate the hemoglobin concentration (g /dL), Quantify the content of total leukocytes (U / L), neutrophils, lymphocytes, eosinophils, monocytes, and basophils, estimate the phagocytic activity (%) and antioxidant activity, (SOD) U.mL-1, for this randomized design (DCA), under controlled laboratory conditions over 55 days, for a total of 6 treatments (0, 1, 2, 3, 4 and 5% of β -glucan in diet) with 3 repetitions (plastic tanks), the doses were determined from results in other works carried out. A density of 15 fish / tank was used, which were placed in 18 tanks operated with 90 L water, for a total of 270 fish. The results were the following in the leukocytes the T6 1.58 × 10³ U / L, hemoglobin in the T2 and T3 being the mean 11.00 (g/dL), in the neutrophils the highest level in the T2 55.00%, for the lymphocytes in T6 51.67%, eosinophils in T2, T4, T6 with the mean of 1.67%, monocytes T3 with 3.33%, and basophils T3 and T4 with the mean of 1.33%. From the results obtained, it was found that ß-glucan in the diet improves the hemoglobin response, leukocyte profile, phagocytic activity and antioxidant activity in juvenile red tilapia. Key words: Hemoglobin, total leukocytes, neutrophils, lymphocytes, phagocytic activity, antioxidant activity